2015
DOI: 10.1590/1413-785220152304147538
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive glass in cavitary bone defects: a comparative experimental study in rabbits

Abstract: OBJECTIVES: To compare bioactive glass and autograft regarding their histomorphometric characteristics. METHODS: The authors conducted a prospective case-control experimental study on animals in order to compare the histomorphometric characteristics of bioactive glass versus autograft. Eight rabbits underwent surgery in which a cavitary defect was created in both proximal femurs. One side was filled with bioactive glass granules and the other, with autograft grafted from the contralateral side. The sides were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…The bioactive material is composed of several ionic compounds (SiO 2 , Na 2 O, CaO, P 2 O 5 ) which when implanted to the receptor surface releases alkaline ions, cause an abrupt pH increase, thus allowing inhibition of bacterial growth through osmotic and acid-base imbalance generated in the local, not being dependent on local antibiotics applications 39,40 . The osteoconductive capacity of bioactive glass has been demonstrated in several previous scientific studies (Table 2) [41][42][43][44][45][46][47][48] , which is consistent with our research data, since it was observed a statistically significant difference in bone neoformation after 14-day and 28-day period in the groups filled with the bioactive glass (submitted or not to PBMT) when compared with the control group AZC. Glass granules can only conduct bone growth efficiently, as long as a direct contact between the glass and the bone can be achieved.…”
Section: Discussionsupporting
confidence: 92%
“…The bioactive material is composed of several ionic compounds (SiO 2 , Na 2 O, CaO, P 2 O 5 ) which when implanted to the receptor surface releases alkaline ions, cause an abrupt pH increase, thus allowing inhibition of bacterial growth through osmotic and acid-base imbalance generated in the local, not being dependent on local antibiotics applications 39,40 . The osteoconductive capacity of bioactive glass has been demonstrated in several previous scientific studies (Table 2) [41][42][43][44][45][46][47][48] , which is consistent with our research data, since it was observed a statistically significant difference in bone neoformation after 14-day and 28-day period in the groups filled with the bioactive glass (submitted or not to PBMT) when compared with the control group AZC. Glass granules can only conduct bone growth efficiently, as long as a direct contact between the glass and the bone can be achieved.…”
Section: Discussionsupporting
confidence: 92%
“…The following histological scoring scale for the presence and intensity of bone formation was used for statistical analysis [29,30]: 1. no osteogenesis, 2. weak osteogenesis, 3. medium-low osteogenesis, 4 medium-high osteogenesis, 5. good-low osteogenesis, 6. good-high osteogenesis, 7. perfect osteogenesis. For this purpose, each slide of histopathological sections was divided into four segments to be observed in detail while the average of the scores of the four quadrants represents the score given to the slide [29].…”
Section: In Vivo Animal Testsmentioning
confidence: 99%
“…Since there were two groups -one was the control and the other was the experimental one treated with BG-gly paste, statistical analysis was performed by using Wilcoxon-Mann-Whitney test [29]. The tests were performed with a level of significance of 5%.…”
Section: In Vivo Animal Testsmentioning
confidence: 99%
“…Preliminary human studies have demonstrated promising results. [76][77][78][79] The current understanding of the differences in biological properties between non-absorbable PMMA and absorbable biomaterials for treatment of PJI is summarized in Fig. 2.…”
Section: Treatment Of Pjimentioning
confidence: 99%